2020
DOI: 10.1371/journal.pone.0243304
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors associated with high prevalence of intimate partner violence amongst school-going young women (aged 15–24years) in Maputo, Mozambique

Abstract: Background In many countries, there is evidence that intimate partner violence is prevalent among young women. This study aimed to determine the prevalence and the factors associated with intimate partner violence in young women (aged 15–24 years) attending secondary schools in Maputo, Mozambique. Method Using a probability proportional sampling strategy, 431 participants were recruited, and the data were collected using a self-administered questionnaire. Binary and multivariate logistic regression analyses … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
13
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(23 citation statements)
references
References 39 publications
7
13
3
Order By: Relevance
“…Similar observations were reported from Nigeria, Uganda, Afghanistan, and Iran suggesting that education and marital status were not associated with domestic violence in pregnancy. 7,9,11,18,23 Our study found no significant association between gestational diabetes and IPV, so agree with Pheiffer et al 27 ; a larger populationbased research is needed to examine this association.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…Similar observations were reported from Nigeria, Uganda, Afghanistan, and Iran suggesting that education and marital status were not associated with domestic violence in pregnancy. 7,9,11,18,23 Our study found no significant association between gestational diabetes and IPV, so agree with Pheiffer et al 27 ; a larger populationbased research is needed to examine this association.…”
Section: Discussionsupporting
confidence: 81%
“…This finding is consistent with those reported in other African countries, including Nigeria and Uganda with prevalence of IPV in pregnancy at 15.1%-31.8%. [7][8][9] However, Faramarzi et al 18 in Iran reported higher prevalence of 59.8%. This observed difference may be attributed to different socio-cultural and religious values between Ghana and Iran.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study finding was lower than a study conducted in the southern part of Ethiopia (wolaita Sodo and Aleta wondo), and a study conducted in Maputo. A cross sectional study which was published recently indicated that the prevalence of life time gender based-violence (GBV), sexual and physical violence were 63.2%, 37.2%, and 56.3%, respectively in Wolaita Sodo town and another study in Aleta wondo reported that lifetime prevalence of gender based violence were 68.2% as well as sexual and physical violence were 26.3% and 56.14% respectively the study conducted in Maputo reported that the lifetime prevalence of gender based violence among school adolescent girls were 55.7% the difference for this might be due to the difference in socio cultural and norms among the study populations besides the difference also might be due to study settings [ 7 , 18 , 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Our study nding was lower than a study conducted in the southern part of Ethiopia (wolaita Sodo and Aleta wondo), and a study conducted in Maputo. A cross sectional study which was published recently indicated that the prevalence of life time gender based-violence (GBV), sexual and physical violence were 63.2%, 37.2%, and 56.3%, respectively in Wolaita Sodo town and another study in Aleta wondo reported that life time prevalence of gender based violence were 68.2 % as well as sexual and physical violence were 26.3% and 56.14% respectively the study conducted in Maputo reported that the life time prevalence of gender based violence among school adolescent girls were 55.7 % the difference for this might be due to the difference in socio cultural and norms among the study populations besides the difference also might be due to study settings (6,15,17)…”
Section: Magnitude Of Gender Based Violencementioning
confidence: 94%